A comparative analysis of the tracking angles and fixed angle systems during sunny and cloudy days under Iraqi conditions - Talib Sabah Hussein; Kadhim Nasir Fadhil; Zaid H. Al-Tameemi (Institute of Advanced Engineering and Science, 2019)
This paper describes design tow systems tracking angles and fixed angle solar panel to improve the performance of solar energy, during the sunny and cloudy days. Depending on the development of the solar tracking system and amount of solar energy captured by the solar panel per day actually, the project is designed with AT 89552 MC depending upon the light falls on (LDR), data will be reading by AT 89552 MC. and changing the direction of a motor in this direction the solar panel will be moving to capture the maximum of solar energy. The tracking angle solar panel has been efficient than a fixed angle. The results show that the tracking angle solar panel has been more efficient than a fixed angle in sunny and cloudy days in morning and afternoon. The tracking angles system generating higher power than the fixed angle system in a morning. The maximum power occurred during the tracking angles system and fixed angle system in the morning, due to drop efficiency of the panels they get heated during the afternoon.